Pengembangan Media Pembelajaran pada Atap Rumah Adat Loura di SMK Negeri 2 Kota Tambolaka Kelas X - Lero, Yuvita Susanti; Kii, Wilhelmus Yape; Making, Samuel Rex Mulyadi; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims: to find mathematical aspects found on the roof of a loura traditional house, apply the mathematical aspects found in learning the roof of a loura traditional house. This research was conducted at SMKN 2 Tambolaka City class X. This type of research is research and development (Research and Development). Data are obtained from the results of filling out observation sheets and, tests and taking documentation. Loura traditional houses have mathematical aspects such as triangles. The results obtained from the implementation of the research showed an increase, this can be seen from the results of student answers on student worksheets and an increase in student activity in terms of questions and answers in class and their active and critical way of thinking. Likewise, the learning outcomes of each action showed improvement. Thus, it can be concluded that the use of learning media in trigonometry material on the roof of a loura traditional house at SMKN 2 Tambolaka City based on the results of research can improve mathematics learning outcomes and teachers can try to apply this method so that students are active and motivated in learning mathematics